پاکستان میں غیر مسلموں سے متعلق ریاستی قوانین : متقدمین اور معاصرفقہا کی آراکی روشنی میں ایک مطالعہState Laws Relating to Non-Muslims in Pakistan: A Study in the Light of Early and Contemporary Jurists (Al-Qamar, 2023)
This article studies state laws of Pakistan relating to non-Muslims in the light of early and contemporary jurists. In the light of the opinions of the early and late jurists, it has become clear that Islam has given all basic human rights to non-Muslims. All the basic rights are also available to them in the Pakistani constitution. After that, there is no need to pass additional laws in Parliament that they cannot convert. We believe that it is a violation of the rights of Muslims in a Muslim state as well as the rights of non-Muslims to try to deprive them of accepting Islam despite the truth of Islam in their hearts.
Keywords: Pakistan; Laws; Non-Muslims; Islamic Sharia